STUDI LITERATUR: STRUKTUR GENOME DAN IDENTIFIKASI GEN YANG BERPERAN DALAM KETAHANAN DEINOCOCCUS RADIODURANS TERHADAP RADIASI - Anisa Oktobianti , Andi; Jamaluddin, Nurbina Septiani; Hala, Yusminah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
Deinococcus radiodurans is an extremophilic bacterium with exceptional resistance to ionizing radiation, oxidative stress, and extreme environmental conditions. This resistance is supported by a unique multipartite genome structure, efficient DNA repair mechanisms, and complex global regulation. Key genes such as recA, ssb, pprA, and irrE play crucial roles in DNA repair and cellular protection. The bacterium can fully reconstruct its genome after severe radiation-induced damage, making it an ideal model for studying DNA repair and stress response mechanisms. Due to its remarkable resilience, D. radiodurans hold great potential for various applications, including radioactive waste bioremediation, radiation protection in medical fields, and advancements in biotechnology and genetic engineering. Further research is necessary to explore its molecular mechanisms and technological applications in industry, healthcare, and environmental sectors.